A study investigating the cutting mechanism of compacted graphite iron based on a novel microstructure of finite element model. (September 2022) - Meng, Fanning; Zhang, Zhenyu; Feng, Jiajian; Gu, Qinming; Wu, Bin; Wang, Jianmei
Abstract: Compacted graphite iron is internationally recognized as a material that has the potential to be applied for preparing high performance engine components. However, difficulties during machinability seriously limit the mass production of these. A novel method based on MATLAB image recognition and python programing was used to establish a microstructural model that included graphite and pearlite particles. The thermal conductivity and specific heat capacity at different temperatures was measured and the results were used to validate the model. Using this novel model, the chip morphology and formation mechanism, cutting surface morphology and formation mechanism and cutting temperature distribution were studied. The simulation results show that crack formation on the chip surface and generation of graphite fragments occurs during the cutting process. The crack opening angle during this is approximately 33°. Significant graphite cavities also appeared on the cutting surface. The stress concentration at the boundary of graphite and pearlite during cutting process was analyzed, and demonstrated to be the primary reason for these phenomena. The temperature of both the rake face and flank face are simulated with the highest cutting temperature concentrated in the secondary deformation zone reaching approximately 322 °C. Furthermore, the simulation results are consistent with the experimental results.